2020
DOI: 10.1016/j.neubiorev.2020.01.020
|View full text |Cite
|
Sign up to set email alerts
|

The neuroethology of spontaneous mimicry and emotional contagion in human and non-human animals

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
143
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 123 publications
(179 citation statements)
references
References 267 publications
9
143
1
2
Order By: Relevance
“…Our study adds to the discussion over the mechanisms underlying the social asymmetry in yawn contagion (for a critical reviews: see Adriaense et al, 2020;Palagi et al, 2020), by showing that yawn contagion is probably associated with bottom-up, rather than with top-down, selective attention. Bottom-up attention is primarily lead by the sensory perception of the eliciting stimulus whereas top-down, selective attention is a voluntary, sustained process in which a particular item is selected internally and focused upon or examined (Katsuki and Constantinidis, 2014).…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Our study adds to the discussion over the mechanisms underlying the social asymmetry in yawn contagion (for a critical reviews: see Adriaense et al, 2020;Palagi et al, 2020), by showing that yawn contagion is probably associated with bottom-up, rather than with top-down, selective attention. Bottom-up attention is primarily lead by the sensory perception of the eliciting stimulus whereas top-down, selective attention is a voluntary, sustained process in which a particular item is selected internally and focused upon or examined (Katsuki and Constantinidis, 2014).…”
Section: Resultsmentioning
confidence: 59%
“…This finding is in line with previous literature. Contagious yawning appears to involve brain areas that are more related to the orienting-bottom up network [temporoparietal junction (TPJ), brainstem nuclei, ventrolateral prefrontal cortex (vlPC)] than top-down related areas [frontal eye fields (FEFs), intraparietal sulcus (IPS), parietal areas; for a review: Palagi et al, 2020]. Moreover, yawn contagion is neither sensitive to the sensory cues present in the signal (auditory, visual, or audio-visual) (Arnott et al, 2009;Norscia and Palagi, 2011) nor affected by the visual perspective of the triggering stimulus (yawns in orientations of 90 • , 180 • , and 270 • are able to trigger yawning responses as frontal, 0 • yawns; Provine, 1989Provine, , 1996.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…chimpanzees, Pan troglodytes 3 ; geladas, Theropithecus gelada 4 ; Tonkean macaques, Macaca tonkeana and Japanese macaques, M. fuscata 5 ; humans, Homo sapiens 6,7 ), spontaneous yawning is considered a plesiomorphic (ancient) trait because its basic motor pattern has been observed in a wide array of vertebrates 8 . On the other hand, contagious yawning between conspecifics has been observed so far in a relatively low number of species, which suggests that this phenomenon may have appeared more recently in vertebrate evolution 9 . In particular, the presence of yawn contagion has been found only in highly social species and seems to be linked to the type of sociality more than to the phylogenetic closeness 9 .…”
mentioning
confidence: 99%
“…In their study, Norscia et al investigate the possible relation between emotional contagion and (auditory) yawn contagion, a form of replication of facial display triggered by an auditory signal. The authors address the affiliation-based accounts (Palagi et al, 2020) and provide evidence supporting the contention that familiarity, gender bias, and social bond drive the rate and efficiency of contagion. The role of the contextual state in the judgment of emotional expression is also addressed by Pinilla et al, who investigate how an induced affective state can affect the judgment of the observed affective state in others, as communicated by face.…”
Section: Explicit and Implicit Emotion Processing: Neural Basis Percmentioning
confidence: 94%